Medical hypnotherapy; even in a tertiary care setting a promising treatment - Bastek, Vanessa B.; Groeneveld, Elroly M.; van Vliet, Michel J. (International Journal of Contemporary Pediatrics, 2022)
Background: Medical hypnotherapy has shown to be an effective treatment in specified conditions such as abdominal pain or headache. Since 2016 the Beatrix children’s hospital, a tertiary care center, offers medical hypnotherapy for a high variety of complex symptom disorders in pediatric patients. Methods: This retrospective COHORT study analyzed the characteristics of pediatric patients treated with medical hypnotherapy in a tertiary care center as well as the effectiveness of the treatment. Results: 214 patients with complex chronic symptoms were treated with medical hypnotherapy. 48% Percent of all patients referred had more than one symptom and 59% of them had had their symptoms for over a year. An overall improvement of symptoms was achieved in 76% of all patients. Conclusions: Medical hypnotherapy seems an effective treatment for patients with multiple chronic and complex symptoms even in a tertiary clinical setting.